Morphological characteristics, chemical and amino acids composition of flours from velvet beans tempe (Mucuna pruriens), an indigeneous legumes from Yogyakarta. Issue 1 (April 2021) - Fitriyah, H; Anwar, F; Palupi, E
Abstract: Velvet beans (Mucuna pruriens) an under-utilized legume which grown predominantly in tropical area, including in Indonesia. The morphological characteristics, chemical and amino acid composition of seeds, fermented velvet beans (Benguk tempeh), and Benguk tempeh flours from the legumes Mucuna pruriens was evaluated to determine their potential practical applications. The seeds of velvet beans contains 12.73±0.10, 4.34±0.33, 25.49±0.06, 3.66±0.03, 3.90±0.06, and 53.79±0.26 (% wb) of moisture, fat, crude protein, ash, crude fiber and carbohydrate, respectively. The mineral content of velvet seeds was 76.38±8.77, 6.64±0.67, and 3.08±0.12 mg 100 g 1 of calcium, iron, and zinc, respectively. Fermentation process on velvet beans into tempeh brings nutritional changes including the breakdown of certain nutrition content and reduction of anti-nutritional compounds. The velvet beans tempeh contains 54.76±0.24, 2.40±0.16, 12.84±0.56, 1.02±0.13, 3.66±0.49, and 28.99±0.60 (% wb) moisture, fat, crude protein, ash, crude fiber and carbohydrate, respectively. The mineral content of velvet beans tempeh was 55.49±13.91, 6.56±0.39 and 2.60±0.33 mg 100 g 1 of calcium, iron, and zinc, respectively. The flours were prepared by steam blanching, oven-drying (60°C) for 7h and milling. The flours contains 13.13±0.52, 6.78±0.72, 25.29±0.41, 0.76±0.04, 4.34±0.32, and 54.06±0.47 (% wb) of moisture, fat, crude protein, ash, crude fiber and carbohydrate, respectively. The mineral content of flour was 29.43±0.00, 5.87±1.36 and 2.56±0.04 mg 100 g" 1 of calcium, iron, and zinc, respectively. The essential amino acids profile of total flour proteins compared favourably with the FAO/WHO reference pattern except for deficiency of sulfo amino acids (methionine and sistin) with concentration of 9.72 mg g 1 crude protein. The flours have potential as flour alternatives for food product development.